Crime Scene classification of Digital Images Sourced from CCTV Footage - Biswas, Saumitra; Bhaumik, Sanchayan; Bag, Tanay (International Journal of Computer Sciences and Engineering, 2026)
CCTV image classification using machine learning algorithm is a novel way of using machine learning for security. This paper investigates how classification can be done using statistical indicators of image pixels without employing extensive image processing techniques. It further performs comparative study of performances of some commonly used classification algorithms in classifying images. The highest performance was by the K-Nearest Neighbor classifier with accuracy, precision, and recall scores of 95%, 90%, and 100% respectively.